Identificación de los factores de riesgos ocupacionales en el área administrativa en la empresa palma oleaginosas del Magdalena a través de la metodología GTC 45 segunda actualización (2020)
The purpose of this degree project is to identify risk factors using the GTC 45 second update, it will be possible to observe which are the occupational risks by determining the level of exposure taking into account the classification and the corresponding values established in GTC 45. This The degree project is made up of 4 specific objectives each with the aim of obtaining optimal and fundamental results for the company Palma oleaginosas del Magdalena, taking into account all the recommendations and specific controls to eliminate or reduce the level of danger, which are determined by the employees of the daily administrative area during their working day while carrying out their work activities.